Eficiência do inseticida thiamethoxam aplicado no momento da colheita da cana-de-açúcar para controle de Mahanarva fimbriolata (Stål.,1854) (Hemiptera: Cercopidae) e seus efeitos na produtividade - FERREIRA, Henrique de Jesus (2009)
The objective of this study was to evaluate the efficacy of the insecticide thiamethoxam in simultaneous application with sugarcane harvest, under mulch, using a mounted sprayer system in the harvester machine and manual application method to control of Mahanarva fimbriolata. The experiments were carried out in the municipal district of Goianésia, Goiás State, in the period from October 2007 to September 2008. Two experiments were carried out set up side by side, in the same area. One experiment was applied using the sugarcane harvester, with a mounted sprayer system set up behind of the harvester, spraying the insecticide over the crop line and covering with mulch right after. The second experiment was applied in the manual method using a backpack sprayer pumped by CO2. The trials were set up in randomized blocks with six replicates. It was tested four rates of thiamethoxam, commercial brand named Actara 250 WG®. The tested rates were: 0 (untreated check), 100, 150 e 200 grams of active ingredient per hectare. The root froghopper infestation in the experiments was evaluated at 35, 75, 127 e 191 days after application. The parameters evaluated at the harvest timing were stalks diameter and yield increase. It was adopted the biometry method to estimate the yield. The M. fimbriolata infestation fluctuated during the evaluated period and the higher infestation level occurred in December and April. It was observed a negative significant correlation between the rates of thiamethoxam and the infestation level of M. fimbriolata to the two application modality. Thiamethoxam provided significative reduction of M. fimbriolata until 191 DAA for all rates, compared to untreated check (dose 0). Regarding the influence of the insecticide in stalks diameter it was observed a significant increment of 10,46% at rate of 100 g of active ingredient per ha when applied in the harvester machine. The treatments did not affect the yield (t ha-1). The application modality of insecticide under mulch, at harvest timing, using a mounted sprayer in the harvester machine showed to be a viable option in the sugarcane crop.